1972
DOI: 10.2136/sssaj1972.03615995003600040026x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water and Temperature on Adsorption of Parathion by Soils

Abstract: Temperature and water effect on the adsorption of parathion (O, O‐diethyl O‐p‐nitrophenyl phosphorothioate) by soils was studied using 14C‐tagged parathion. The parathion was applied in aqueous solutions and in hexane over a concentration range of 1–10µg/ml. It was found that the parathion is adsorbed by soils from aqueous solution without any appreciable thermic effect. In a dry soil‐hexane‐parathion system the slightly polar parathion molecules efficiently compete with the apolar hexane molecules for adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 0 publications
6
46
0
Order By: Relevance
“…Temperature and the purity of water and solute can also influence solubility measurements. Bowman and Sans (1977) reported a water solubility for parathion of 12.9 ppm at 20°C, and Yaron and Saltzman (1972) found a value of 4.3 ppm at 10°C. The commonly quoted literature value Is 24 ppm at 25°C (Gunther et al 1968).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and the purity of water and solute can also influence solubility measurements. Bowman and Sans (1977) reported a water solubility for parathion of 12.9 ppm at 20°C, and Yaron and Saltzman (1972) found a value of 4.3 ppm at 10°C. The commonly quoted literature value Is 24 ppm at 25°C (Gunther et al 1968).…”
Section: Resultsmentioning
confidence: 99%
“…Kahn (1977) reported that Freundlich k values for the adsorption of fonofos on cation saturated humic acid decreased as temperature increased. This observation indicated that adsorption was exothermic; however, Yaron and Saltzman (1972) found no appreciable thermic effects in parathion adsorption if a correction was made for the increased water solubility at higher temperatures.…”
Section: +mentioning
confidence: 92%
“…At low water content, sorption sites of the inorganic surfaces can effectively sorb organic compounds, however, at high water content, sorption of organic compounds is controlled by soil organic matter. Adsorption of a number of organic and volatile organic compounds (VOCs) has been found to be greater as soil moisture decreases (Hance, 1977;Bailey and White, 1964;Yaron and Saltzman, 1977;Estrella et al, 1993;Steinberg and Kreamer, 1993). Studies have shown that soil water content drastically inhibits vapor-phase sorption given that the solubility of the tested gas in water is low.…”
Section: Factors Affecting Sorptionmentioning
confidence: 99%
“…Water substantially reduces the surface activity of the inorganic surfaces by occupying the high-energy sorption sites. The polar water molecules have a greater affinity for available sorption sites on soils than the nonpolar organics (Yaron and Saltzman, 1977;Hance, 1965). The polar water molecules tend to reduce organic compound sorption, although, organics will sorb, even under saturated condition, because of their hydrophobic behavior (their tendency to avoid the polar water molecules in solution).…”
Section: Factors Affecting Sorptionmentioning
confidence: 99%
See 1 more Smart Citation